Peran Local Champion Dalam Pengembangan Pariwisata Berbasis Komunitas Di Balkondes Tuksongo, Wringinputih, dan Giritengah - Yuwono, Ardian Indro; Yuwono, Ardian Indro; Putrianti, Herni; Putrianti, Herni (JURNAL DESTINASI PARIWISATA, 2022)
Community leaders or local champion have important role for develop tourist villages and community empowerment processing. Balai Ekonomi Desa (Balkondes) program is a community-based tourism development program which implemented at villages around Borobudur. This article explains the role of government, stakeholders, and the role of local champions in mediating, facilitating and mobilizing the community. This study used qualitative research methods through in-depth interviews using snowball techniques. The themes emerged from this research, the role of PT.TWC is to initiate the program and connect to BUMN as a partners to each village. The selection or presence of local champions is determined through an informal process. In each village represented by one supervisor becomes a local champion who plays an important role. Keyword: local champion; balkondes; pariwisata berbasis komunitas